Examining the immunoreactivities of the receptor-binding domain of SARS-CoV-2 spike proteins using a panel of human monoclonal antibodies - Tan, Jie Ling (Nanyang Technological University, 2022)
Previously, a panel of human monoclonal antibodies (hMAbs) (PD5, SC23, and PD4) were isolated from convalescent patients to evaluate their therapeutic potential in the treatment of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). As the binding domains of these antibodies have not been mapped, this study will examine the binding domains of the antibodies by analysing the immunoreactivities of cells expressing different domains of the spike protein of SARS-CoV-2. Results showed that PD5 and SC23 bound to the receptor-binding domain (RBD) and the S1 subunit of the spike protein while PD4 does not. Two local SARS-CoV-2 isolates had mutations at or near the Furin Cleavage Site of their spike proteins after passaging in Vero E6 cells and these isolates showed different infection patterns in Vero E6 cells. One isolate had an R682W substitution mutation while the other had a 675QTQTN679 deletion mutation, this study examines if these mutations affect the Furin cleavage of the spike proteins. Using the panel of hMAbs, the immunoreactivities of cells that only express the spike proteins of the isolates were examined. Results suggests that the R682W mutation hindered Furin cleavage and could be responsible for the differences in infection patterns between the isolates.